Effect of introducing virtual community and community group buying on customer’s perceived value and loyalty behavior: A convenience store-based perspective - Xu, Xiaoyu; Hu, Zhineng (Frontiers in Psychology, 2022)
Customers’ declining receptivity to conventional marketing tools has been a challenge for convenience stores. To overcome this, retailers are turning to social media as a new, potent marketing tool for creating business prospects and encouraging direct customer interaction. However, it is still unknown how social media marketing affects the shifts in customer behavior. This paper expands on the relationship of “loyalty program (LP) + virtual community experience → perceived value → customer loyalty” in the traditional convenience store scenario, refining the variables of virtual community experience, perceived value, and customer loyalty. It also compares the effectiveness of different LP design structures (reward amounts × reward time limits) and explores the mediation impact of program loyalty and the moderation effect of alternative attractiveness. The results demonstrate the superior performance of LPs with an expiry policy and differential returns and highlight the importance of enhancing members’ virtual community experiences in fostering customer perceived value and loyalty. The results also show the minor negative moderation impact of community group buying and prove that emotional value significantly impacts customer loyalty. Still, the social value does not affect program loyalty. The recommendations are offered, such as designing growing-oriented and periodical zeroing LPs, as well as using new social media marketing tools (virtual community-based marketing) to empower traditional marketing techniques (LP-based relationship marketing) and constructing a “convenience store + community group buying” model. The findings have substantial theoretical and practical implications for traditional convenience stores in properly implementing loyalty and social media marketing tactics to maximize customer value and loyalty with a limited budget.